Nurses' Knowledge Of Patient Safety Incidents: Literature Review - Seriga, Seriga; Hassan, Hafizah Che; Sansuwito, Tukimin (International Journal of Health Sciences, 2024)
Knowledge is a convention in forming an action in a nurse which greatly influences the performance of the nurse herself in implementing and carrying out actions for patient safety in the hospital. One of the ways in which the implementation of patient safety is to ensure that incidents that threaten patient safety do not occur or that there is the potential to result in injury to patients that should not occur. The aim of this literature review is to understand and describe the situation regarding nurses' knowledge of patient safety incidents. The review of this paper is the result of a literature study in the form of analysis using the systematic mapping study method through searches from Google Scholar which determined 6 national journals. The results of the study show that good nurse knowledge will influence the performance of nursing care which has an impact on patient safety incidents. The conclusion that can be drawn from this study is that there is a correlation between nurses' knowledge of patient safety incidents and commitment which is very necessary in efforts to build patient safety. Suggestion: it is hoped that we will not only research the relationship between knowledge and patient safety incidents but also nurses' compliance in implementing patient safety.